Cognitive Biases in Pathological Health Anxiety: The Contribution of Attention, Memory, and Evaluation Processes. (May 2016) - Witthöft, Michael; Kerstner, Tobias; Ofer, Julia; Mier, Daniela; Rist, Fred; Diener, Carsten; Bailer, Josef
Pathological health anxiety refers to the medically unfounded fear of suffering from a severe illness. Differences in cognitive processes related to attention, memory, and evaluation of health threat have been hypothesized to underlie pathological health anxiety. In no study, however, have researchers systematically and simultaneously assessed different cognitive biases. On the basis of the idea that multiple cognitive biases simultaneously contribute to psychopathology (the combined-cognitive-bias hypothesis), we compared 88 patients with pathological health anxiety, 52 patients with depressive disorder, and 52 healthy participants on their performance in several cognitive tasks involving health-threatening content. Individuals with pathological health anxiety showed a stronger attentional bias to health-threat-related information, more negative explicit (but not implicit) evaluations of health threat, and biased response behavior in light of health threat. The results suggest that stronger bindings between feelings of arousal and health-threatening information in working memory might be crucial for the higher salience of health-threatening contents in pathological health anxiety.